Reflection and feedback in ambulatory education. (August 2014) - Okubo, Yumiko; Nomura, Kaoru; Saito, Hiroshi; Saito, Noboru; Yoshioka, Toshimasa
Summary Background It has been argued that the best method of acquiring clinical reasoning is through seeing new out‐patients. The purpose of this interventional study was to establish a clinical clerkship course for Japanese medical students in an out‐patient care setting, with multiple opportunities for reflective practice and improving the clinical reasoning abilities of the students. The effectiveness of the course was also examined. Methods Students performed examinations of new patients and made diagnostic decisions in 20 minutes. They presented their case using the SNAPPS (Summarize the case, Narrow the differential, Analyze the differential, Probe the preceptor, Plan management, and Select an issue for self directed learning) method, and this was followed by feedback from faculty members using the 1–minute preceptor method and a mini clinical evaluation exercise (mini‐CEX). Students' clinical reasoning abilities were assessed by the objective structured clinical examination (OSCE) and the script concordance test (SCT). Students' written comments and responses to an interview about the course were also analysed. Cross‐sectional data were examined by comparing individual OSCE and SCT scores, and the multiple‐choice question examination (MCQ) completed by students who did and did not participate in this project. Results Students in the programme had higher scores on the mini‐CEX in all areas. The SCT and OSCE scores were also significantly higher than the scores for the control group. Students' comments about the course, which provided an opportunity for daily reflection, were positive. Discussion Students rapidly acquired clinical reasoning skills through reflective practice. Students also demonstrated motivation to learn through the examination of new patients. The clinical clerkship programme with multiple opportunities for reflective practice in an out‐patient care setting substantially improved the clinical reasoning abilities of medical students.